Phase 1 study of dalotuzumab monotherapy and ridaforolimus–dalotuzumab combination therapy in paediatric patients with advanced solid tumours. (July 2016) - Frappaz, Didier; Federico, Sara M.; Pearson, Andrew D.J.; Gore, Lia; Macy, Margaret E.; DuBois, Steven G.; Aerts, Isabelle; Iannone, Robert; Geschwindt, Ryan; Van Schanke, Arne; Wang, Rui; Geoerger, Birgit
Abstract: Aim: Dalotuzumab is a highly specific, humanised immunoglobulin G1 monoclonal antibody against insulin-like growth factor receptor 1. This multicenter phase 1 study (NCT01431547 ) explored the safety and pharmacokinetics of dalotuzumab monotherapy (part 1) and the combination of dalotuzumab with the mammalian target of rapamycin inhibitor ridaforolimus (part 2) in paediatric patients with advanced solid tumours. Methods: Dalotuzumab was administered intravenously every 3 weeks starting at 900 mg/m 2 and escalating to 1200 and 1500 mg/m 2 . Combination therapy included intravenous dalotuzumab at the defined single-agent recommended phase 2 dose (RP2D) and oral ridaforolimus 28 mg/m 2 daily (days 1–5), repeated weekly. Pharmacokinetic studies were performed to evaluate the mean serum trough dalotuzumab concentration, which guided the RP2D. Results: Twenty-four patients were enrolled (part 1, n = 20; part 2, n = 4). No dose-limiting toxicities were observed in patients receiving dalotuzumab alone. One patient experienced dose-limiting stomatitis in the combination arm. Pharmacokinetic data showed dose-dependent increases in exposure (area under the curve from zero to infinity [AUC0–∞ ]) (87, 900, 164, 000, and 186, 000 h*mg/ml for the 900, 1200, and 1500 mg/m 2 dose levels, respectively), maximum serum concentration (Cmax ) (392, 643, and 870 mg/ml), and serum trough concentration (Ctrough ) (67.1, 71.6, and 101 mg/ml). The mean half-life was 265, 394, and 310 h, respectively. Dalotuzumab pharmacokinetics were not affected by coadministration with ridaforolimus. One of six patients with Ewing sarcoma had confirmed partial response to dalotuzumab monotherapy at 900 mg/m 2 . Time to response was 41 d, and progression occurred at 126 d. Conclusion: Dalotuzumab was well tolerated in paediatric patients with advanced solid malignancies. The RP2D of dalotuzumab is 900 mg/m 2 (ClinicalTrials.gov identifier:NCT01431547, Protocol PN062). Highlights: No dose-limiting toxicities with single-agent dalotuzumab. Pharmacokinetic data were similar to previous data reported in adults. No pharmacokinetic interactions for combination of dalotuzumab and ridaforolimus. Dalotuzumab and ridaforolimus warrant further evaluation in paediatric patients. An objective response to dalotuzumab was observed in one patient with Ewing sarcoma.